Pengaruh Habit dan Performance Expectancy terhadap Purchase Intention - Tri Adhi Santoso; Almadana, Aulia Vidya (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Habit or consumer habit nowadays is to check Whatsapp apps in a short period of time, whereas it caused individual to be influenced after seeing uploaded content, with no exception for sales ads content. The purpose of this study was to conduct empirical testing of the influence of habit and performance expectations on purchase intention. This study uses a structural equation model (SEM) to test the hypotheses of 278 respondents according to the research criteria. The results shown that habit and performance expectancy were positively related to purchase intention.